Preparation of sub-micron PZT particles with the sol-gel technique - Linardos, S.; Zhang, Qi; Alcock, Jeffrey R. (Elsevier, 2006)
This paper describes the production of Pb1.0Zr0.9Ti0.1 ceramic powder, by using metal organic precursors as starting materials. In this study polyvinylpyrrolidone, PVP, was used to create a PZT–PVP sol and then also added as a secondary stage to control the particle size of the powder. Two different sol–gel routes were used to create PZT powder. Both routes gave similar primary particle sizes in the range, 30–70 nm, but different agglomerate formations. Perovskite PZT powder was created with both routes.